HIGH SCHOOL AND MEDIA EDUCATION IN LIQUID MODERNITY: : DIALOGY AND INTERDISCIPLINARITY - M. M. Gaidargi, Alessandra (Revista Gênero e Interdisciplinaridade, 2021)
This theoretical-conceptual article addresses the relationship between education for the media and liquid modernity, pointing out dialogicity and interdisciplinarity as possible paths for the establishment of a teaching-learning process with young students of High School. This study presents a structured theoretical framework on the concepts of dialogue and dialogicity by Paulo Freire and the conditions of liquidity and fluidity of modern societies by Zygmunt Bauman, contextualized on the current moment of society, specifically in the context of secondary school aimed at education of young people. In the considerations, we point out the viability of Freire's dialog and interdisciplinarity as a path towards an education for the media integrated to reality and receptive to the changes and continuous updates of knowledge demanded by liquid modernity, offering an emancipatory and liberating education proposal based on the integration between school and all types of media available.